Efficacy and safety of therapeutic strategies for human brucellosis: A systematic review and network meta-analysis. - Sarah Nascimento Silva; Gláucia Cota; Diego Mendes Xavier; Glaciele Maria de Souza; Marina Rocha Fonseca Souza; Moisés Willian Aparecido Gonçalves; Felipe Francisco Tuon; Endi Lanza Galvão (Public Library of Science (PLoS), 2024)
Background Human brucellosis is a neglected, re-emerging, and endemic zoonosis in many countries. The debilitating and disabling potential of the disease is a warning about its morbidity, generating socioeconomic impact. This review aims to update the current evidence on the efficacy and safety of therapeutic options for human brucellosis using the network meta-analysis (NMA). Methodology A systematic search was conducted in four different databases by independent reviewers to assess overall therapy failure, adverse events, and time to defervescence associated with different therapies. Randomized clinical trials (RCTs) evaluating any therapeutic drug intervention were selected, excluding non-original studies or studies related to localized forms of the disease or with less than 10 participants. Data were analyzed by frequentist statistics through NMA by random effects model. The risk of bias and certainty of evidence was assessed, this review was registered at PROSPERO. Results Thirty-one (31) RCTs involving 4167 patients were included. Three networks of evidence were identified to evaluate the outcomes of interest. Triple therapy with doxycycline + streptomycin + hydroxychloroquine for 42 days (RR: 0.08; CI 95% 0.01-0.76) had a lower failure risk than the doxycycline + streptomycin regimen. Doxycycline + rifampicin had a higher risk of failure than doxycycline + streptomycin (RR: 1.96; CI 95% 1.27-3.01). No significant difference was observed between the regimens when analyzing the incidence of adverse events and time to defervescence. In general, most studies had a high risk of bias, and the results had a very low certainty of evidence. Conclusions This review confirmed the superiority of drugs already indicated for treating human brucellosis, such as the combination of doxycycline and aminoglycosides. The association of hydroxychloroquine to the dual regimen was identified as a potential strategy to prevent overall therapy failure, which is subject to confirmation in future studies.